Evaluating the Effects of Community-based Organization Engagement on HIV and AIDS-related Risk Behavior in Kenya - Riehman, Kara.S. (Taylor and Francis, 2013)
International donors have increasingly shifted AIDS funding directly to community-based organizations (CBOs) with the assumption that responding to the epidemic is best achieved at the community level. The World Bank, ICF Macro, and the National Council for Population and Development in Kenya, conducted a study to evaluate the community response in Kenya. The study used a quasi-experimental design comparing seven study communities and seven comparison communities in Nyanza Province and Western Province. We examined the impact of CBO activity on individual and community-level outcomes, including HIV knowledge, awareness and perceptions, sexual risk behavior, and social transformation (gender ideology and social capital). The study consisted of two components: a household survey conducted in all 14 communities, and qualitative data collected in a subset of communities. Individuals in communities with higher CBO engagement were significantly more likely to have reported consistent condom use. Higher CBO engagement was associated with some measures of social capital, including participation in local and national elections, and participation in electoral campaigns. CBOs provide added value in addressing the HIV and AIDS epidemic in very targeted and specific ways that are closely tied to the services they provide (e.g., prevention education); thus, increasing CBO engagement can be an effective measure in scaling up prevention efforts in those areas.